Applying food frequency questionnaire to evaluate the dietary pattern and life style on women with breast cancer - Huda H. Alabbody; Ban S. Al- Nasiry; Khalida H. Kadhim (مجلة كلية الطب, 2018)
Background: Breast cancer is the most common cancer among women and ranked number two after lung cancer in the world. According to the World Health Organization, breast cancer accounts for 22.9% among cancers in women in 2012. Objective: This study was designed to evaluate the dietary pattern particularly dairy products consumption and the role of lifestyle on women with breast cancer in Baghdad city and its suburbs. Subjects and Methods: The study was conducted on 100 women with breast cancer, as a case group, compared with a control group comprised of 100 healthy women. Demographic data were collected from both groups. A food frequency questionnaire was used of 33 items of foods for reporting the dietary pattern and modes of life style of the participants. The statistical Chi-square test / SPSS V.22 was used to analyze the data. Results: Our data show that 71% of the women in the two groups were found to be overweight with body mass index (BMI 25-29.9). 90% of obese women represented in case group (BMI ≥30), while 82% of normal weight women (BMI 18.5-24.9) were in control group. Approximately 61% of women in both groups were in post-menopausal age. Intake of high fatty dairy products by the participants showed a statistically significant increase in breast cancer risk (OR=1.625, CIs 95%=0.686-3.847). Consumption of vegetables and fruits was significantly lower (P˂0.01) in case group than in the control group. Furthermore, roughly 68% women in the case group used to smoke cigarettes. In addition, lack or decreased regular physical exercises (never with ≥1 practice per wk) was statistically significant (OR= 44. 809; CIs= 5.889 –340.963). Other parameters, including long period of breastfeeding, early age at first birth and consumption of white meat, beans and eggs were all reported to have significance. On the other hand, there was no correlation with the marital status, occupation, living area, class of dairy products, and passive smoking. Conclusion: Unhealthy dietary habits especially high-fat dairy intake and wrong lifestyle may be risk factors and predispose Iraqi women for breast cancer development. Therefore, eating healthy food and following correct lifestyle are highly recommended as a suitable program for the prevention of breast cancer.